Enhancing Chinese steamed bread: A comprehensive review of food ingredients and their impact on physical characteristics, rheological properties, and nutritional composition - Abdul Aziz, A.H; Zainol, M.K.; Putra, N.R; Mamat, H (Rynnye Lyan Resources, 2025)
Chinese steamed bread is made from wheat flour and water as the main ingredients and fermented with yeast. In recent years, significant progress has been made in incorporating innovative food additives into Chinese steamed bread (CSB) to improve its overall quality and meet the changing demands of modern consumers. This review provides an overview of these advances, focusing on the effects of food additives on the physical and rheological properties of the dough and the nutritional composition of the final CSB products. The knowledge gained from these studies was presented in a cohesive manner, allowing for a detailed discussion of the various aspects relevant to the production and analysis of Chinese steamed bread. By examining the latest research on the use of additives, this report aimed to identify potential ways to improve the sensory properties, nutritional profile, and overall appeal of CSB. It serves as a valuable resource for future research efforts to improve the quality and appeal of CSB